ATL marketing and its impact on brands- a case study on Ogilvy & Mather Bangladesh - Islam, Nusrat Binte (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.